2019
DOI: 10.1089/thy.2018.0212
|View full text |Cite
|
Sign up to set email alerts
|

JAK/STAT3 and NF-κB Signaling Pathways Regulate Cancer Stem-Cell Properties in Anaplastic Thyroid Cancer Cells

Abstract: Background: Anaplastic thyroid carcinoma (ATC) is still one of the most aggressive and refractory cancers, and a therapy with a new concept needs to be developed. Recently, the research of cancer stem cells (CSCs) has been progressed, and CSCs have been suggested to be responsible for metastasis, recurrence, and therapy resistance. In ATC-CSCs, aldehyde dehydrogenase (ALDH) activity is the most reliable marker to enrich the CSCs; however, it itself is just a marker and is not involved in CSC properties. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Sherry-Lynes et al found that the transcription regulator STAT3 can directly bind to the JMJD3 promoter, specifically inducing JMJD3 expression and resulting in demethylation of H3K27me3, thereby affecting the expression of downstream genes that have been proven to be related to chemosensitivity. Ken Shiraiwa et al suggested that STAT3 played an important role in ATC stem cells (Shiraiwa et al, 2019). After treatment with a STAT3 inhibitor, cancer cells were sensitized to chemotherapeutic drugs (Borbone et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Sherry-Lynes et al found that the transcription regulator STAT3 can directly bind to the JMJD3 promoter, specifically inducing JMJD3 expression and resulting in demethylation of H3K27me3, thereby affecting the expression of downstream genes that have been proven to be related to chemosensitivity. Ken Shiraiwa et al suggested that STAT3 played an important role in ATC stem cells (Shiraiwa et al, 2019). After treatment with a STAT3 inhibitor, cancer cells were sensitized to chemotherapeutic drugs (Borbone et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer stem-like cells are the small population of cells within the tumor that are well known for their important role in carcinogenesis, cancer resistance, recurrence and self-renewal [13,69,70]. Among the many laboratory models in use for the study of cancer stem-like cells, the one involving the growth of cancer cells on ultralow attachment plates is a widely accepted model for the generation of spheres.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer stem cells (CSCs) are a small population of cells present in tumors that play a critical role in cancer resistance, relapse, tumorigenesis and poor clinical outcomes [13]. This information led us to investigate whether SNG can suppress the stemness of PTC CSC-like cells derived from BCPAP and TPC-1 spheroids (thyrospheres).…”
Section: Sng Attenuates Stemness Potential Of Ptc Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylated STATs then binds to specific DNA elements and activates gene transcription (Murray, 2014). Specifically, the JAK2/STAT3 signaling pathway plays crucial roles in the EMT, apoptosis, proliferation, and drug resistance of various cancers (B. Li & Huang, 2017; Yu, Gong, Li, Pan, & Zhang, 2018), and the activation of STAT3 is closely related to the stemness of cancer cells (Kuepper et al, 2019; Shiraiwa et al, 2019). However, whether the JAK2/STAT3 pathway regulates EMT and the stemness of OSCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%